Pulse plating of Pd–Ag alloy films from deep eutectic solvents. (2nd December 2019) - Manolova, Mila; Böck, Reinhard; Scharf, Ingolf; Mehner, Thomas; Lampke, Thomas
ABSTRACT: In water based solutions, electrodeposition of Pd and Pd alloys is complicated due to hydrogen embrittlement. This can be avoided by using non-aqueous solutions like deep eutectic solvents (DES). In this study, the electrodeposition of Pd–Ag films were investigated on Cu from choline chloride/urea based deep eutectic solvents containing sulfosalicylic acid dihydrate (SSS) as an organic additive. The effects of pulse current, an organic additive and different Ag concentrations on the surface morphology and layer thickness were evaluated. Cyclic voltammetry experiments showed that the reduction of Pd(II) occurred prior to that of Ag(I). Scanning electron microscope (SEM) micrographs of the deposits revealed that the surface of the Pd–Ag films were typically granular to nodular and became more compact when the surface active compound was present in the DES solution. X-ray diffraction (XRD) experiments proved the existence of metallic Pd–Ag alloys.